Disruptive innovation and the long run impact of mobile lending on bank sustainability in Zambia and Kenya - Nonyane, Kgahliso Bridget (University of the Witwatersrand, Johannesburg, 2022)
The emergence of financial technology companies (fintechs) in the past decade has provided new twists on financial models, allowing customers more influence on their financial outcomes. As financial innovations disrupt financial services across the globe, many banks face the risk of reduced competitive advantage. In response, banks are exploring strategic alliances with Mobile Network Operators (MNOs) and fintechs to maintain their competitive advantage and enter new markets. One such innovation is the use of mobile phones to conduct financial transactions and tap into new markets. Mobile banking adoption studies predominantly focus on financial inclusion and its critical role in economic development and less on the potential transcendental impact that adoption of other mobile banking functions, such as mobile lending, might have on the banks’ affluent customer segment. More specifically, knowledge on whether mobile lending is a complementary or disruptive innovation for banks in the long term remains unclear. Firms that have managed to successfully develop or leverage on disruptive innovations were only able to determine the disruptiveness of the innovation ex post and scholars that have attempted to identify disruptive innovations ex ante, found it challenging. This research took a pre-emptive look at the long run impact of mobile lending on banks in Africa. Specifically, the case for mobile lending in Zambia and Kenya was assessed one of the four large multinational African banks in Zambia and Kenya. The literature review evaluated the theory of disruptive innovation as well as the Base of the Pyramid (BoP) theory as they were relevant to the establishment of mobile lending as a complementary or disruptive innovation for banks. An explanatory sequential mixed-methods design was adopted. A quantitative analysis of the secondary data for Zambia and Kenya for 2017 - 2019 was analysed, which was followed by in-depth, semi-structured interviews with ten participants from various business units (and various levels) within the bank. This allowed for the exploration of the main reasons for the quantitative analysis findings as well as provided additional insights
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Innovation Studies to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Disruptive Innovations; Mobile lending; Disruptive Innovations; Fintechs; Affluent Segment; BoP; Proactive Cannibalisation; UCTD; SDG-9: Industry, innovation and infrastructure